Rationality in prophylactic central neck dissection in clinically node-negative (cN0) papillary thyroid carcinoma: Is there anything more to say? A decade experience in a single-center. (May 2017) - Dobrinja, C.; Troian, M.; Cipolat Mis, T.; Rebez, G.; Bernardi, S.; Fabris, B.; Piscopello, L.; Makovac, P.; Di Gregorio, F.; de Manzini, N.
Abstract: Aim: Papillary thyroid carcinoma (PTC) is the most common thyroid malignancy. Despite its extremely favorable prognosis, cervical lymph node metastases are a common feature of PTC and a known independent risk factor for local recurrence. However, the role of prophylactic central neck dissection (PCND) remains a matter of debate in patients with clinically node-negative (cN0) PTC. To better clarify the current role of PCND in the surgical treatment of PTC, evaluating advantages and disadvantages of PCND and outcome of cN0 PTC patients who have been treated with either total thyroidectomy alone or in combination with PCND. A review of recent literature data is performed. Methods: Between January 2000 and December 2015, 186 consecutive patients with cN0 PTC were identified to be included in the present study. 74 of these underwent total thyroidectomy associated with PCND, while 112 patients underwent total thyroidectomy alone. The epidemiological and clinical-pathological data of all patients included were collected at diagnosis and during follow-up. Results: Overall complication rate was significantly higher in the group of patients undergoing PCND (39.2% vs. 17.8%, p = 0.0006). To be specific, they presented a considerably increased risk of temporary recurrent laryngeal nerve injury ( p = 0.009) and of permanent hypothyroidism ( p = 0.016). Overall survival and recurrence rates did not differ between those undergoing PCND and those undergoing total thyroidectomy alone ( p = 1.000 and p = 0.715, respectively). Conclusions: The results of the present study do not support the routine use of PCND in the treatment of cN0 PTC patients. Highlights: The role of prophylactic central neck dissection (PCND) remains a matter of debate in patients with clinically node-negative (cN0) PTC. Overall complication rate was significantly higher in the group of patients undergoing PCND. Overall survival and recurrence rates did not differ between those undergoing PCND and those undergoing total thyroidectomy alone. Accurate patient selection is important to achieve the best results.